2020
DOI: 10.3390/ijerph17030986
|View full text |Cite
|
Sign up to set email alerts
|

The Intercontinental Terminals Chemical Fire Study: A Rapid Response to an Industrial Disaster to Address Resident Concerns in Deer Park, Texas

Abstract: On Sunday, 17 March 2019, a fire erupted at the Intercontinental Terminals Company (ITC, Deer Park, La Porte, TX, USA), resulting in a large fire that blazed for several days. In response, we rapidly launched disaster response activities to monitor air pollutants (total volatile organic compounds (TVOCs), fine particulate matter (PM2.5), black carbon (BC), and ultra-fine particles (UFPs) during the fire in two affected communities. To assess immediate health effects and residential air quality, we also rapidly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 27 publications
(35 reference statements)
0
13
0
Order By: Relevance
“…The ITC fire resulted in a sustained release of a variety of contaminants to both ambient air and surface water 9 . While most direct exposure to the public from such an incident is likely from inhalation 7 , exposure due to surface water is also possible as the Houston Ship Channel is used for recreation. For instance, several public parks provide access to this massive body of water, and anglers are commonly seen in the area despite the presence of fish advisories 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ITC fire resulted in a sustained release of a variety of contaminants to both ambient air and surface water 9 . While most direct exposure to the public from such an incident is likely from inhalation 7 , exposure due to surface water is also possible as the Houston Ship Channel is used for recreation. For instance, several public parks provide access to this massive body of water, and anglers are commonly seen in the area despite the presence of fish advisories 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies assessed the releases of pollutants during the ITC Fire accident. An Han et al 7 investigated air quality and health concerns of affected residents over a 6 week period following the accident. While this study found no elevations in the air concentrations of benzene, total volatile organic compounds, or particular matter (2.5 μm diameter), a small-size (13 individuals) health effects survey identified mild respiratory and post-traumatic stress disorder symptoms during the fire and two weeks afterwards.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies by that group documented increased symptoms, outpatient visits, and medication use for respiratory disease, including asthma, during this same OAP incident [16,17]. Increased respiratory symptoms were reported by nearby residents during and for several weeks after a large industrial fire in Texas, US, which burned and released PM2.5 and black carbon into the atmosphere for several days [18]. A recent meta-analysis confirmed reports of an increased incidence of asthma in first responders involved in rescue and recovery following the attack and fire on the World Trade Center in the US [19].…”
Section: Literature Reviewmentioning
confidence: 58%
“…Increased respiratory symptoms were reported by nearby residents during and for several weeks after a large industrial fire in Texas, US, which burned and released PM 2.5 and black carbon into the atmosphere for several days [18]. A recent meta-analysis confirmed reports of an increased incidence of asthma in first responders involved in rescue and recovery following the attack and fire on the World Trade Center in the US [19].…”
Section: Literature Reviewmentioning
confidence: 88%